Platelet-Rich Plasma Intramuscular Injections — Antinociceptive Therapy in Myofascial Pain Within Masseter Muscles in Temporomandibular Disorders Patients: A Pilot Study - Nitecka-Buchta, Aleksandra; Walczynska-Dragon, Karolina; Kempa, Wojciech Michal; Baron, Stefan (Frontiers in Neurology, 2019)
Background and objectives: The objective of this study was to explore the nociceptive effect of platelet-rich plasma (PRP) intramuscular injections in myofascial pain of masseter muscles. Methods: Patients diagnosed with myofascial pain were assessed for eligibility for the study. Masticatory muscle disorder was diagnosed based on the Research Diagnostic Criteria for Temporomandibular Disorders (Ia and Ib). A total of 80 patients with diagnosed masticatory muscles disorder were enrolled in the study; 58 of them (21 male and 37 female, 29.4 ± 6.53 years old) met the inclusion criteria and were randomly allocated to one of the two groups: Group I (n = 29) and Group II (n = 29). The first group received injections with PRP and the second group received injections with isotonic saline as the control group (0.9% NaCl). The Visual Analog Scale (VAS) was used to determine the pain intensity changes during each follow-up visit in each group. Results: A statistically significant improvement in pain intensity was achieved: 58% reduction in the experimental group and 10.38% in the control placebo group on Day 5. Pain levels (VAS) 14 days after the injections were slightly increased (47.16% and 4.62% respectively, for PRP group and the placebo group). Conclusions: Intramuscular injection of PRP was a successful method for reducing myofascial pain within masseter muscles in temporomandibular disorders patients. However, the use of PRP for the treatment of myofascial pain within masticatory muscles requires further, reliable clinical trials. Trial Registration: Bioethical Commission at the Silesian Medical Chamber in Katowice, Poland 44/2017 as well as at ClinicalTrials.gov NCT03323567 (December 13, 2017).